Ethnomedicinal knowledge of Baiga and Gond Tribe and plant diversity in Jagmandal Forest, Mandla, India, with phytosociological diversity and utilization strategies (Asian Journal of Ethnobiology, 2024)
Abstract. Jhariya BL, Pawar M. 2024. Ethnomedicinal knowledge of Baiga and Gond Tribe and plant diversity in Jagmandal Forest, Mandla, India, with phytosociological diversity and utilization strategies. Asian J Ethnobiol 7: 13-21. In the interior areas of the Mandla District, plants become the source of medicine because of a lack of facilities and remoteness. A medicinal exploration was made to find out the medicinal values of common plants present in the Jagmandal Forest of Mandla District (Mandla, India) during 2020-2023. During the survey, a total of 162 plant species belonging to 64 families were identified as being used for treatment of approximately 43 ailments or therapeutic indications which highest study done so far in the area. It has also been observed that more numbers of medicinal plants were recorded in the family Fabaceae. The majority of plant parts used to prepare treatments for various illnesses were leaves, as evidenced by the fact that leaves were the most often employed component of the plant against various diseases, followed by herbs (42%), trees (33%), climbers (14%), and shrubs (11%). The disease category with the highest ICF value (0.81) was the antiseptic. Aloe vera, Achyranthus aspera, and Azadirachta indica were highly preferred as treatments. More photochemical studies are needed before some of them can be used as drugs to benefit mankind. It is critical to explore, identify, and use new medicinal plants while also assisting in the conservation of existing but threatened species of rare medicinal plants in the area with the support of local communities.
Keywords: Ailments, conservation, local communities, Madhya Pradesh, Mandla, medicinal plant